2010
DOI: 10.1530/eje-09-0878
|View full text |Cite
|
Sign up to set email alerts
|

Serum glucose and insulin are associated with QTc and RR intervals in nondiabetic elderly

Abstract: Aims: To study whether nondiabetic persons with impaired fasting serum glucose and hyperinsulinemia have QTc/QT interval prolongation and RR interval shortening in the electrocardiogram (ECG), and whether these were associated with an increased risk of sudden cardiac death. Methods: This study consisted of two analyses. First, a cross-sectional analysis was used as part of the population-based Rotterdam Study including 1050 men and 1520 women (R55 years) without diabetes mellitus. Participants in round 3 of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 37 publications
2
30
1
Order By: Relevance
“…The insulin-induced hypokalemia will also decrease the repolarization reserve by a reduction of the rapid delayed rectifier current I Kr (36), thus further increasing the risk of cardiac arrhythmia and cardiac arrest (34). Furthermore, in a population-based study of 2,570 elderly people without diabetes it was demonstrated that hyperinsulinemia was associated with significantly increased QT interval and increased risk of sudden death (37). In addition, a recent study revealed that QT prolongation and hypokalemia were common in diabetic patients with severe hypoglycemia, which increased their risk of fatal arrhythmia and death (38).…”
Section: Discussionmentioning
confidence: 99%
“…The insulin-induced hypokalemia will also decrease the repolarization reserve by a reduction of the rapid delayed rectifier current I Kr (36), thus further increasing the risk of cardiac arrhythmia and cardiac arrest (34). Furthermore, in a population-based study of 2,570 elderly people without diabetes it was demonstrated that hyperinsulinemia was associated with significantly increased QT interval and increased risk of sudden death (37). In addition, a recent study revealed that QT prolongation and hypokalemia were common in diabetic patients with severe hypoglycemia, which increased their risk of fatal arrhythmia and death (38).…”
Section: Discussionmentioning
confidence: 99%
“…26 Importantly, it has also been shown that a prolonged QTc interval is associated with increased risk for sudden cardiac death in these ambulatory populations. 27 A postulated mechanism underlying the glucose-QTc interval relationship is parasympathetic tone, namely heart rate variability. 26 …”
Section: Discussionmentioning
confidence: 99%
“…Insulin may play a particular role in this context, since bariatric surgery has been shown to rapidly reduce circulating insulin levels [24]. Moreover, several previous cross-sectional studies have revealed an independent association between circulating insulin levels and QTc interval length [25,26]. Interventional studies, however, have revealed a less consistent picture where intravenous insulin infusion acutely increased QTc interval length in normal weight [27] but not in obese subjects [28] under euglycemic conditions.…”
Section: Introductionmentioning
confidence: 99%